Replication of an acutely lethal simian immunodeficiency virus activates and induces proliferation of lymphocytes. - Fultz, P N (1991)
A variant of simian immunodeficiency virus from sooty mangabey monkeys (SIVsmm), termed SIVsmmPBj14, was previously identified and shown to induce acute disease and death within 1 to 2 weeks of inoculation of pig-tailed macaques and mangabey monkeys (P. N. Fultz, H. M. McClure, D. C. Anderson, and W. M. Switzer, AIDS Res. Hum. Retroviruses 5:397-409, 1989). SIVsmmPBj14 differed from its parent virus, SIVsmm9, not only in pathogenicity but also in multiple in vitro properties. As a first approach to understanding the biological and molecular mechanisms responsible for the acute disease and death induced by this variant, virus-host cell interactions of SIVsmmPBj14 and SIVsmm9 were studied. Initial rates of replication of the two viruses were identical in primary peripheral blood mononuclear cells (PBMC) from normal pig-tailed macaques and mangabey monkeys, but SIVsmmPBj14 infection always resulted in higher yields of virus than did SIVsmm9 infection, as assessed by levels of reverse transcriptase activity in culture supernatants. Surprisingly, despite its cytopathicity for macaque and mangabey CD4+ cells, replication of SIVsmmPBj14 was accompanied by up to 10-fold increases in number of viable cells compared with cell numbers in uninfected or SIVsmm9-infected cultures. Furthermore, SIVsmmPBj14 was shown to infect and replicate in resting PBMC just as efficiently as in mitogen-stimulated PBMC, irrespective of whether exogenous interleukin-2 (IL-2) or antibodies that neutralized IL-2 were added to culture media. Accumulation of virus in culture supernatants of resting PBMC preceded by several days the appearance of activated cells which expressed the IL-2 receptor alpha subunit (CD25), suggesting that activation of cells was not essential for replication. The ability to activate and to induce simian PBMC to proliferate appeared specific for the acutely lethal variant because incorporation of [3H]thymidine by PBMC from naive animals was observed only upon incubation with concentrated, heat-inactivated SIVsmmPBj14 and not with other viruses. Both CD4(+)- and CD8(+)-enriched cell populations proliferated in response to SIVsmmPBj14. These results are consistent with in vivo observations and suggest that the abilities both to replicate in resting cells and to induce lymphocytes to proliferate may contribute to the extreme virulence of SIVsmmPBj14.